Sejarah Kepimpinan Warisan Khadijah Binti Khuwalid - Kiftiah, Suwelda; Syahid, Abdul; Dakir, Dakir (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
Khadijah bint Khuwailiid (556–619 CE), a prominent Quraysh woman, was an extraordinary figure in Islamic history, renowned for her exceptional leadership. Born into a wealthy, charitable family that upheld high moral values, she inherited and led her family's business following her father's death. Khadijah managed international trade with integrity and fairness, demonstrating her leadership not only in business but also in her role as the wife of Prophet Muhammad (PBUH). As the Prophet’s foremost supporter during the early propagation of Islam, Khadijah provided unwavering moral, spiritual, and material support. She was the first person to embrace Islam, encouraging the Prophet during the initial challenges of his mission. Her humility, courage, and wisdom made her a role model for Muslim women. Khadijah's leadership legacy remains relevant today, inspiring values of courage, independence, and dedication. She played a pivotal role in the development of Islam and set an example of how women can lead in various spheres of life. Her passing in the tenth year of prophethood left a profound impact, solidifying her role as